Methanolic Fenugreek Seed Extract Induces p53-Dependent Mitotic Catastrophe in Breast Cancer Cells, Leading to Apoptosis - Alrumaihi FA; Khan MA; Allemailem KS; Alsahli MA; Almatroudi A; Younus H; Alsuhaibani SA; Algahtani M; Khan A (Dove Medical Press, 2021)
Faris A Alrumaihi1Masood A Khan2Khaled S Allemailem1Mohammed A Alsahli1Ahmad Almatroudi1Hina Younus3Sultan A Alsuhaibani1Mohammad Algahtani4Arif Khan2 1Department of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi Arabia; 2Department of Basic Health Sciences, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi Arabia; 3Interdisciplinary Biotechnology Unit, Aligarh Muslim University, Aligarh, India; 4Department of Laboratory Medicine, Security Forces Hospital, Mecca, Saudi Arabia   Purpose: The plant Trigonella foenum-graecum, well-known as fenugreek, has been shown to control type-2 diabetes, the level of cholesterol, inflammation of wounds, disorders related to gastrointestinal tracts, and cancer as well. The present study aimed to evaluate the anticancer potential of methanolic fenugreek seed extract (FSE) and its possible molecular mechanism of action in breast cancer cells.Methods: The anticancer potential of FSE was evaluated in MCF-7 and SK-BR3 breast cancer cells through various cellular assays after selecting the IC10, IC25, IC35, and IC50 doses by the cell cytotoxicity assay. Furthermore, the oral acute toxicity of FSE was examined in mice, according to the guidelines of the Organization for Economic Cooperation and Development (OECD).Results: FSE exhibited dose-dependent cytotoxicity, as the IC50 was found to be 150 and 40 μg/mL for MCF-7 and SK-BR3 breast cancer cells, respectively. The cytological observations showed the typical apoptotic morphology in both of the breast cancer cells upon treatment with FSE, as it inhibited the migration and adhesion, in a dose-dependent manner. The flow cytometry analysis revealed that FSE induced a significant shift from G2/M, and polyploidy (>G) at higher concentrations that suggested the activation of p53-mediated mitotic catastrophe, consequently leading to apoptosis. FSE induced a significant increase in the mitochondrial depolarization, ROS as well as a Bax/Bcl-2 ratio, and also exhibited the mitochondrial associated p53 signaling pathway. The in vivo acute toxicity data revealed that the oral administration of FSE did not induce any toxic effect in mice. Conclusion: This study, for the first time, reports the mechanistic details of the anti-cancer potential of FSE. It requires a detailed analysis to understand the effect of FSE to induce the apoptosis through the multiple signaling pathways at varying concentrations. The nontoxic effect of FSE in mice suggests to utilize it safely for pharmaceutical formulations in different cancer systems. Keywords: fenugreek seed extract, breast cancer cells, mitotic catastrophe, apoptosis, p53 signaling, mitochondria-associated pathway, oral acute toxicity